The Community empowerment of mud crab fishing through the establishment of a joint business group - Handayani, Handayani; Gunaisah, Endang; Ulat, Muhammad Ali; Katili, Vicky; Mustasim, Mustasim; Poltak, Hendra (Community Empowerment, 2021)
Mangrove areas have high economic potential that support community welfare. However, crab fishermen have not enjoyed welfare because the conversion of mangrove ecosystems reduces the quantity of fish caught, fishing facilities are inadequate, and the marketing of the catch is not well distributed. Problem solving is carried out through initial surveys, Focus Group Discussions, and training accompanied by evaluation and follow-up. The results of the activity revealed that the crab fishing community had understood the material provided and a Joint Business Group was formed as a follow-up to the fishery instructor. In the future, the formed Joint Business Group needs to be provided with assistance to be more independent.